2018
DOI: 10.1007/s00125-018-4741-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum kidney injury molecule 1 and β2-microglobulin perform as well as larger biomarker panels for prediction of rapid decline in renal function in type 2 diabetes

Abstract: Aims/hypothesisAs part of the Surrogate Markers for Micro- and Macrovascular Hard Endpoints for Innovative Diabetes Tools (SUMMIT) programme we previously reported that large panels of biomarkers derived from three analytical platforms maximised prediction of progression of renal decline in type 2 diabetes. Here, we hypothesised that smaller (n ≤ 5), platform-specific combinations of biomarkers selected from these larger panels might achieve similar prediction performance when tested in three additional type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 33 publications
10
41
1
1
Order By: Relevance
“…The key findings from this study across the range of CKD stages were that serum biomarkers improve the prediction of future eGFR and progression to <30 ml min −1 [1.73 m] −2 beyond baseline eGFR. As in our past studies [11,21,22], a large number of the biomarkers evaluated showed highly significant associations with eGFR and its decline. However, almost all of the predictive information could be obtained using just a few of these intercorrelated biomarkers.…”
Section: Discussionsupporting
confidence: 70%
“…The key findings from this study across the range of CKD stages were that serum biomarkers improve the prediction of future eGFR and progression to <30 ml min −1 [1.73 m] −2 beyond baseline eGFR. As in our past studies [11,21,22], a large number of the biomarkers evaluated showed highly significant associations with eGFR and its decline. However, almost all of the predictive information could be obtained using just a few of these intercorrelated biomarkers.…”
Section: Discussionsupporting
confidence: 70%
“…Reference intervals for sKIM-1 are lacking for healthy individuals. McWiliams et al reported also diurnal variation of uKIM-1 levels, with higher values in the morning than in the evening [30]. In contrast, we found negative correlation of uKIM-1 with age.…”
Section: Discussioncontrasting
confidence: 62%
“…In humans, the usefulness of blood (serum/plasma) KIM-1 was documented in AKI and CKD [21,26,28]. Circulating KIM-1 strongly predicted progression of CKD in patients with type 1 and type 2 diabetes [26,29,30] and was useful in allograft nephropathy [31]. A recent study by Schultz et al has also shown that pKIM-1 may predict the future decline of estimated glomerular filtration rate (eGFR) and risk of CKD in healthy middle-aged participants [32].…”
Section: Discussionmentioning
confidence: 99%
“…for this purpose. Most of tested new biomarkers, for example CRP, ferritin, adiponectin, fetuin, have predicted progression of hepatosteatosis or CVD , whereas others like KIM‐1 (kidney injury molecule 1) and B2M (β 2 ‐microglobulin) have predicted a rapid decline in kidney function . However, the overall effect of such markers on top of eGFR has been modest .…”
Section: Biomarkersmentioning
confidence: 99%